Social Values and Character Education in the Novel Rasa by Tere Liye - Dessy Dellasari; Yessi Fitriani; Muhammad Ali (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to identify and analyze the character education values and social values embedded in Tere Liye's novel Rasa. A descriptive qualitative approach was employed using content analysis techniques, focusing on character portrayal, storyline development, and interactions among characters within the novel. The analysis revealed diverse social values, including caring, helping others, compassion, social responsibility, honesty, and cooperation. Dominant character education values identified encompassed religious attitudes, discipline, independence, hard work, appreciation of achievement, social concern, honesty, and responsibility. Through characters such as Linda, Bunda, Kak Adit, and Joan Bam Punjabam, the narrative demonstrates how individual character formation is profoundly shaped by social environment and life experiences. The research provides a comprehensive dual-analysis framework that simultaneously examines both character education values and broader social values within a single contemporary literary work, offering integrated insights into their interconnection. The novel can serve as a valuable pedagogical resource for educators seeking to cultivate moral awareness and character development in students through literary engagement. This study affirms literature's educational function beyond entertainment, contributing to the fields of literary pedagogy and character education by demonstrating how narrative fiction can effectively transmit cultural and moral values to readers.